Alat-Alat Produksi Masyarakat Ainu dalam Manga Golden Kamuy Karya Satoru Noda - Tresna Dharma, I G N Arya; Luhur Wedayanti, Ni Putu; Laksmita Sari, Ida Ayu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 2 No 1 (2020)DO - 10.24843/JS.2020.v02.i01.p01, 2020)
This study aims to determine production tools from technological systems of Ainu community in Satoru Noda’s Golden Kamuy manga. The theory used in this research are the theory of anthropological literature by Endraswara (2013), theory of universal cultural elements by Koentjaraningrat (2015) and the semiotics theory by Peirce (1955). The literature study method used as data collection method. The founded data analysed by adjusting the existing of the concepts and theoretical framework. The results of the analysed data presented using descriptive analysis method. The results of analysed data summarized in conclusion with informal method. The obtained result of this research are 4 production tools from technological systems of Ainu community that are represented in the Golden Kamuy manga, such as itata-ni, attush-karabe, isete-ni, and rauomap which is have a role in facilitating the life of Ainu community in obtaining and processing natural product for daily needs.